Exercise Related Proteinuria in Children - Angoorani, Hooman; Farmanara, Hamedreza; Sobouti, Behnam; Izadpanahi, Mohammad; Nejati, Parisa (Journal of Pediatric Nephrology, 2019)
Transient proteinuria in children can be idiopathic or secondary to exercise or fever. Exercise related proteinuria usually is derived from low renal blood flow to the kidneys. It usually is defined as urinary protein excretion higher than 100-150 mg/m2/day and ends 24 hours after exercise. The intensity of exercise has a main role in the amount of protein excreting in the urine. It usually is transient. However, further assessment is needed to exclude systemic diseases if proteinuria is present besides hematuria, if it does not disappear after 48 hours, or if more than 1 gram of protein is excreted from the urine in a day. Keywords: Proteinuria; Exercise; Child.